2017
DOI: 10.1111/bjh.14751
|View full text |Cite
|
Sign up to set email alerts
|

Platelets stored at 4°C contribute to superior clot properties compared to current standard‐of‐care through fibrin‐crosslinking

Abstract: Summary Currently, platelets for transfusion are stored at room temperature (RT) for 5–7 days with gentle agitation, but this is less than optimal because of loss of function and risk of bacterial contamination. We have previously demonstrated that cold (4°C) storage is an attractive alternative because it preserves platelet metabolic reserves, in vitro responses to agonists of activation, aggregation and physiological inhibitors, as well as adhesion to thrombogenic surfaces better than RT storage. Recently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
138
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(147 citation statements)
references
References 53 publications
7
138
2
Order By: Relevance
“…Cold storage is known to increase the activation of integrin αIIbβ3 under basal conditions . However, the 4 days of RT storage prior to refrigeration appears to confer some resistance to cold‐induced activation of integrin αIIbβ3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold storage is known to increase the activation of integrin αIIbβ3 under basal conditions . However, the 4 days of RT storage prior to refrigeration appears to confer some resistance to cold‐induced activation of integrin αIIbβ3.…”
Section: Discussionmentioning
confidence: 99%
“…Cold storage of platelets is an attractive methodology as it ameliorates many of the issues inherent to RT storage . Studies have shown that platelet refrigeration reduces the risk of bacterial proliferation, decreases platelet metabolic activity and minimises the release of biological response modifiers (BRMs) . Furthermore, cold storage provides the advantage of potentially extending the platelet shelf life .…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for the preference for LTOWB compared to components includes the fact that LTOWB is a more concentrated product compared to reconstituted whole blood (WB) using components (due to increased additive solutions in each component) . LTOWB also contains cold platelets (PLTs) that are more hemostatically active compared to the use of PLTs stored at room temperature when components are used . The risk of bacterial contamination of room temperature PLTs is also greatly reduced with the use of cold‐stored WB.…”
mentioning
confidence: 99%
“…Over the past decade, cold storage (1‐6°C) of PLTs has generated renewed interest as an alternative to room temperature (RT; 20‐24°C) storage due to its superior preservation of hemostatic function. Compared to RT‐stored PLTs (RTP), cold‐stored PLTs (CSP) have been shown to have better in vitro aggregation response, form stronger clots, maintain mitochondrial function, produce similar amounts of MPs, and respond to physiologic inhibitors (i.e., prostacyclin and nitric oxide) . CSP also have a proven track record in patients, showing acute hemostatic superiority over RTP in individuals with thrombocytopenia, aspirinated volunteers, and in cardiac surgery patients .…”
mentioning
confidence: 99%